Hospitalisation Utilisation and Costs in Schizophrenia Patients in Finland before and after Initiation of Risperidone Long-Acting Injection. (7th May 2012) - Asseburg, Christian; Willis, Michael; Löthgren, Mickael; Seppälä, Niko; Hakala, Mika; Persson, Ulf
Abstract : Objectives . Quantify changes in hospital resource use in Finland following initiation of risperidone long-acting injection (RLAI). Materials and Methods . A retrospective multi-center chart review (naturalistic setting) was used to compare annual hospital bed-days and hospital episodes for 177 schizophrenia patients (mean age 47.1 years, 52% female, 72% hospitalized) before and after initiation of RLAI (between January 2004 and June 2005) using the within-patient "mirror-image" study design. The base case analytical approach allocated hospital episodes overlapping the start date entirely to the preinitiation period. In order to investigate the impact of inpatient care ongoing at baseline, the change in bed-days was also estimated using an alternative analytical approached related to economic modelling. Results . In the conventional analysis, the mean annual hospitalisation costs declined by €11, 900 and the number of bed-days was reduced by 40%, corresponding to 0.19 fewer hospital episodes per year. The reductions in bed-days per patient-year were similar for patients switched to RLAI as inpatients and as outpatients. In the modelling-based analysis, an 8% reduction in bed-days per year was observed. Conclusion . Despite uncertainty in the choice of analytic approach for allocating inpatient episodes that overlapping this initiation, consistent reductions in resource use are associated with the initiation of RLAI in Finland.